v.1.0_LA_4D_Flow - Spartera, M S; Hess, A T (University of Oxford, 2020)
MATLAB-based software for post-processing of left atrial flow parameters acquired 4D Flow cardiovascular magnetic resonance. The software was coded by Dr. A. Hess (OCMR) with input from Dr. M. Spartera and Dr. A. Stracquadanio.